2012
DOI: 10.1088/0967-3334/33/5/787
|View full text |Cite
|
Sign up to set email alerts
|

Addressing the computational cost of large EIT solutions

Abstract: Abstract. Electrical Impedance Tomography (EIT) is a soft field tomography modality based on the application of electric current to a body and measurement of voltages through electrodes at the boundary. The interior conductivity is reconstructed on a discrete representation of the domain using a FEM mesh and a parametrization of that domain. The reconstruction requires a sequence of numerically intensive calculations. There is strong interest in reducing the cost of these calculations.An improvement in the com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 37 publications
0
12
0
Order By: Relevance
“…One significant contribution to the computational cost is solving the forward problem using the finite element model (FEM) (Boyle et al 2012). The FEM is widely used to obtain the numerical solution of the forward problem in EIT by incorporating domain geometry, boundary conditions and prior information about the conductivity distribution.…”
Section: Introductionmentioning
confidence: 99%
“…One significant contribution to the computational cost is solving the forward problem using the finite element model (FEM) (Boyle et al 2012). The FEM is widely used to obtain the numerical solution of the forward problem in EIT by incorporating domain geometry, boundary conditions and prior information about the conductivity distribution.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the Kohonen map showed advantages over the classical reconstruction methods in terms of performance (good resolution accuracy) with the possibility to sense tactile inputs in real-time (in average 20 ms versus 262 ms for EIDORS using the difference imaging of EIT). Although it has been reported that the difference EIT image reconstruction technique can be very fast and can achieve 40 − 50Hz [65], the computational cost or complexity of EIT reconstruction techniques has been shown to be a drawback when the matrix size augments [66]. The computational complexity of EIT methods requires to inverse one matrix of dimension n, which costs computationally at least O(n 2 × m), where m is the number of finite elements of the FEM, which means that as the matrix augments -, the size of the tactile sheet and the number of electrodes,-the computational time for image reconstruction will increase asymptotically.…”
Section: Resultsmentioning
confidence: 99%
“…The 2-D rank-one update was 7.1 times faster than the 2.5-D method across most mesh sizes, which is accounted for by the numerical integration implied by (13). There are likely to be further gains from optimizing this implementation for multiple processing cores because key portions of the Jacobian calculation ( 14), ( 15), ( 26), ( 29) can be performed in parallel and the Jacobian typically consumes a significant portion of the total calculation time in each Gauss-Newton iteration (Boyle et al 2012b). Mesh density was measured as the inverse of the maximum element height h (elements per metre) for both 2-D and 3-D meshes.…”
Section: -D P O S I T I O N Ja C O B I a Nmentioning
confidence: 99%